The Role of International News Websites in Defining the Features of International Politics Towards the Kurdistan Region A Field Study for A Group of Journalists in The Kurdistan Region - Baran Muhammed Abdullah; Habeeb Malalla Ibrahim (Zanco Journal of Humanity Sciences)
International news websites play a key role in determining international policies. This study is for selecting the role of the international websites of change and formulating international policies.